Pengaruh Terapi Musik Klasik Dan Murotal Terhadap Penurunan Tingkat Depresi Pada Lansia - Rossyam Wardani.S, Ike; , Maskun Pudjianto, SMPh., S.Pd., M.Kes; , Sugiono, S.Fis., M.HKes (2015)
Background: Depression is a psychological disorder that most commonly occurs in the last years of life of the individual. Depression among the elderly affect shorten life expectancy by exacerbating physical deterioration in the elderly, the fulfillment of developmental tasks elderly, lowering the quality of life of the elderly, emotionally and financially draining people affected and their families and support systems sosisal has. Physiotherapist program are given in the elderly who experience depression among others are listening to classical music and murottal. Objective: This study aimed to investigate the influence of classical music and murottal therapy to decrease the rate of depression in the elderly. Methods: This research method using a quasi-experimental research design with pre and post test with control group design. The number of samples used is 10 people. Results: Statistical test using the Wilcoxon test with the results obtained there is the influence of classical music and murottal therapy to decrease the rate of depression in the elderly premises p = 0.042 (<0.05). As for the influence of different test p value = 0.035 (<0.05). Conclusion: With these results we can conclude there is the influence of classical music and murottal therapy to decrease the rate of depression in the elderly.